PENERAPAN STRATEGI PEMBELAJARAN AKTIF KARTU ARISAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 9 PEKANBARU - Raffica Zahara; Roza Linda; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Active learning strategy of arisan card to improve student learning achievement in class XI IPA SMAN 9 Pekanbaru has done. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of group XI IPA3 as the experimental group and students of group XI IPA1 as the control group. Experimental group is a group that is applied to active learning strategy of arisan card while the control group was not. Strategy of arisan card is a strategy that uses the principles of arisan, where there is a question card and an answer card . Cards are in the matter of the roll to be drawn and the card answers have been given to students in groups randomly. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount> ttable is 3,22>1.67, means that the application of active learning strategy of arisan card can improve student learning achievement on the topic of colloid in class XI IPA SMAN 9 Pekanbaru. The category improvement of student achievement at experiment group was high category with N-gain normalized is 0,80.Keywords: arisan card, Active Learning, Learning achievement, Colloid